Optimizing Timing and Preparation for Allogeneic Hematopoietic Stem Cell Transplantation in Higher-Risk Myelodysplastic Syndromes - Geng L; Chen E; Ji Y; Liu H; Sun Z (Blood and Lymphatic Cancer: Targets and Therapy, 2025)
Liangquan Geng,1,* Erling Chen,2,* Yanping Ji,3,* Huilan Liu,1 Zimin Sun1,2,4 1Department of Hematology, The First Affiliated Hospital of University of Science and Technology of China, Hefei, People’s Republic of China; 2Institute of Hematology and Blood Diseases Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Tianjin, People’s Republic of China; 3Department of Hematology, Affiliated Hospital of Jiangsu University, Zhenjiang, People’s Republic of China; 4Blood and Cell Therapy Institute, Division of Life Sciences and Medicine, Anhui Provincial Key Laboratory of Blood Research and Applications, University of Science and Technology of China, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zimin Sun, Department of Hematology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, No. 17 Lujiang Road, Luyang District, Hefei, Anhui, 230001, People’s Republic of China, Email zmsun@ustc.edu.cnIntroduction: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only curative treatment for higher-risk myelodysplastic syndromes (MDS), but optimal timing and donor selection remain controversial.Methods: We conducted a retrospective analysis of 70 higher-risk MDS patients classified by the revised International Prognostic Scoring System (IPSS-R) undergoing allo-HSCT. Patients were stratified by: 1) the interval from diagnosis to allo-HSCT (early: < 6 months vs later: ≥ 6 months); 2) pre-transplant treatment cycles (fewer: < 2 vs more: ≥ 2); 3) remission status (complete remission [CR] / partial remission [PR] vs non-remission [NR]), and 4) donor type (sibling vs unrelated cord blood [UCB]).Results: The results showed a significantly higher 3-year overall survival (OS) in the early HSCT group (70% vs 50%, p = 0.05) with lower transplant-related mortality (TRM) (22.7% vs 46.5%, p = 0.0205). Although more pre-transplant treatment cycles were linked to a lower relapse rate (2.3% vs 15.4%, p = 0.0403), they did not significantly affect OS or TRM. Early HSCT emerged as the only significant factor influencing both OS (Hazard Ratio [HR] 2.84, p = 0.01) and TRM (HR 3.21, p = 0.01). While no significant differences were noted between sibling HSCT and unrelated cord blood transplantation (UCBT) for OS and TRM, UCBT demonstrated a lower incidence of chronic graft-versus-host disease (cGVHD) (19.0% vs 52.9%, p = 0.003).Discussion: Our findings suggest early allo-HSCT may optimize outcomes in higher-risk MDS. In settings where sibling donors are unavailable, UCBT could serve as a potential alternative, though this observation requires validation in prospective multicenter studies to account for inherent selection biases and confounding factors.Keywords: allogeneic hematopoietic stem cell transplantation, myelodysplastic syndromes, higher-risk